Remediasi Miskonsepsi Kinematika Gerak Lurus dengan Pendekatan STAD - Yaspin Yolanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study aims to 1 find out the percentage change of kinematic misconscope of motion straight after remediation, 2 Student Response in remediation implementation with cooperative learning approach Student Team Achievement Division class 10 MAN 1 Model Lubuklinggau. Subjects were 21 students based on purposive sampling technique based on previous research conducted by Novitasri. The research method used is descriptive qualitative. Technique of data collecting done by triangulation that is diagnosis understanding student concept, interview and questionnaire of student response in learning. Remediation of misconceptions with cooperative learning approach Student Team Achievement Divisions showed that from 17 items tested before remediation mean misconception percentage 80,11 percent and after remediation to 37,53 percent 42.58 percent. Student response after remediation using STAD learning is very good. Keyword: Miskonsepsi, Remediasi, STAD